Professor М. V. Vinokurov about the railways’ wagon parkdevelopment of national railways - N. V. Ustiak (History of science and technology, 2018)
The article is devoted to the vision by professor М. V. Vinokurov the process on development of the railways wagon park in the Russian empire and soviet time (up to 1960). All aspects of con-structing freight wagons and passenger carriages are shown chronologically. М. V. Vinokurov de-fined directions in the development of carriages constructions. Further development and improve-ment of railway transport included foremost radical reconstruction of traction - replacement of locomotives by electric locomotives and diesel engines. On this basis the rearmament of all railway transport industries was carried out, including wagon and carriage facilities.